2020
DOI: 10.1371/journal.pone.0228556
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins (HSP 90, 70, 60, and 27) in Galleria mellonella (Lepidoptera) hemolymph are affected by infection with Conidiobolus coronatus (Entomophthorales)

Abstract: Invertebrates are becoming more popular models for research on the immune system. The innate immunity possessed by insects shows both structural and functional similarity to the resistance displayed by mammals, and many processes occurring in insect hemocytes are similar to those that occur in mammals. The humoral immune response in insects acts by melanization, clotting and the production of reactive oxygen species and antimicrobial peptides, while the cellular immunity system is based on nodulation, encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…We also observed a downregulation in HSP70 expression in the fat body in response to C. militaris infection. Previous studies reported either an increase in HSP expression in different tissues of G. mellonella after infection with B. bassiana and Conidiobolus coronatus , or no change compared to uninfected insects [ 7 , 61 , 81 ]. These inconstancies may be caused by differences in pathogenesis that occur after infection with different fungal species and strains.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a downregulation in HSP70 expression in the fat body in response to C. militaris infection. Previous studies reported either an increase in HSP expression in different tissues of G. mellonella after infection with B. bassiana and Conidiobolus coronatus , or no change compared to uninfected insects [ 7 , 61 , 81 ]. These inconstancies may be caused by differences in pathogenesis that occur after infection with different fungal species and strains.…”
Section: Discussionmentioning
confidence: 99%
“…Chaperones are key proteins for correctly folding and assembling newly synthesized proteins and make them have stereoisomerism, which makes AMPs have cell selectivity and can prevent cytotoxicity. According to a previous review: both pyrhocoricin and drosocin can prevent DnaK from refolding misfolded proteins by inducing a permanent closure of the DnaK peptide-binding cavity (Kragol et al, 2001;Le et al, 2017;Wrońska and Boguś, 2020).…”
Section: Inhibition Of Protein Biosynthesismentioning
confidence: 99%
“…These two HSPs are primarily regulated by PGA 1 , not heat shock. Treating the cells with an inhibitor of cyclooxygenase, aspirin, did not influence the HSP70 levels when the cells were maintained at their standard growth temperature (28 • C) but upregulated their synthesis at a higher temperature of 37 • C. HSPs act in a variety of immunoregulatory roles at the intracellular and extracellular levels [99,100].…”
Section: Eicosanoid-related Signalingmentioning
confidence: 99%
“…AMPs typically appear in hemolymph of infected insects about 6-12 h after infections. Other chemicals include lysozymes, oxygen and nitrogen-free radicals, stress-related proteins, and enzyme cascades, including the PPO pathway [33,41,99,100]. Humoral responses have been activated against bacterial, fungal, and viral infections.…”
Section: Antimicrobial and Antiviral Humoral Responsesmentioning
confidence: 99%